Station Rotation Type Blended Learning Model Against Critical Thinking Ability of Fourth Grade Students - Dwicky Putra Nugraha, Dewa Made (Universitas Pendidikan Ganesha, 2020)
This study is conducted based on the problem of the low critical thinking skills of grade 4th students of SDK . It is presumed because the learning model applied is less relevant to the students' need. The model that expected can solve the problem is the blended learning station rotation model. This study investigates critical thinking difference between students with blended learning rotation models and students with conventional learning toward fourth-grade students of SDK KaryaSingaraja. The instrument of data collection is a critical thinking skill test in the form of an essay. The data is analyzed descriptively. The hypothesis is tested by using t-test polled variance. The study results show that the experiment group's mean score is 81,28 and higher than the control group, 65,5. Meanwhile, it gains score tvalue (5,21) >ttable(2,00) with 5% significant(0,05). The result shows a significant difference between students with blended learning rotation models and students with conventional learning. It can be concluded that the blended learning rotation model positively affects the critical thinking of the fourth-grade students of SDK . Appropriate learning model selection affects students' critical thinking.